If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -27 = -17 Reorder the terms: -27 + 2y = -17 Solving -27 + 2y = -17 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 2y = -17 + 27 Combine like terms: -27 + 27 = 0 0 + 2y = -17 + 27 2y = -17 + 27 Combine like terms: -17 + 27 = 10 2y = 10 Divide each side by '2'. y = 5 Simplifying y = 5
| -83=5y-28 | | -5(B-4)=5B+20 | | -4.6+2.5=-3.8x+2.7 | | 14-8N=-2(5N-2) | | -5(7-3X)=19-3X | | -20-5P=5(4-5P) | | -6N-N=14 | | -8=-2P+6P | | K+3+6=11 | | 0=X-4-5X | | 2x+3+4x+1= | | -3N+3-6N=3 | | -4V-3V=-14 | | x(n-3)=4 | | 1+-.5= | | 1+.5x= | | 18x^2-27=35 | | 1.5(x+1)+3.5(x+1)=7.5 | | x^2+5x-10=-3x+10 | | 6x^2+2x-15=34-33x | | 28=4/7w | | 1/2w+3/4w | | 2-2=9x+2x | | 2e^4x-3=5 | | Ln(x)+ln(6)=2 | | 6=8s-3/4-20 | | -1+a/5=-4 | | 6x^2-2x+4=24 | | 8m+3=5m+18 | | x+(x*0.0975)=25 | | x^2-7x+4=-6 | | (-50)x(-4)= |